To solve the quadratic equation \(x^2 - 18x = -80\), we can go through the parts of the problem systematically.
Part A:
To make the equation a perfect square trinomial, we can use the formula for completing the square. A perfect square trinomial takes the form \((x - h)^2 = k\).
- Start with \(x^2 - 18x\).
- Take half of the coefficient of \(x\) (which is \(-18\)), divide by \(2\), and square it: \[ \left(\frac{-18}{2}\right)^2 = (-9)^2 = 81 \]
- Therefore, to make \(x^2 - 18x\) a perfect square, we need to add \(c = 81\) to both sides: \[ x^2 - 18x + 81 = -80 + 81 \] This simplifies to: \[ x^2 - 18x + 81 = 1 \]
Answer Part A:
Value of \(c\): 81
Part B:
Now we can factor the left side: \[ (x - 9)^2 = 1 \]
Answer Part B:
The equation is rewritten as: \((x - 9)^2 = 1\)
Part C:
To solve for \(x\), we take the square root of both sides: \[ x - 9 = \pm 1 \]
This gives us two equations:
- \(x - 9 = 1\)
- \(x - 9 = -1\)
From the first equation: \[ x = 10 \]
From the second equation: \[ x = 8 \]
Answer Part C:
Lesser number: 8
Part D:
From the values we found in Part C, the greater number is:
Answer Part D:
Greater number: 10